47 Dual Tasking in Older Women: Physical Activity or Else?. (20th December 2019) - Muhaidat, Jennifer; Al-Yahya, Emad; Mohammad, Maha; Qutishat, Dania; Okasheh, Rasha; AL-Khlaifat, Lara; Dawes, Helen; Lawrie, Sophie; Esser, Patrick
Abstract: Background: The interplay between gender, Physical Activity (PA) and Dual Task (DT) gait in older adults is unclear. This study aimed to address DT gait based on gender and PA level in older adults. Methods: Gait measures were collected using an Inertial Measurement Unit (IMU) during the 10-meter and Timed Up and Go (TUG) tests in single and DT conditions. Global Physical Activity Questionnaire (GPAQ) was used to measure PA. A total of 120 community-dwelling older adults (81 women and 39 men) took part. Participants were divided according to gender and PA level into four groups (women achieving (WA = 31), women not achieving (WN = 50), men Achieving (MA = 29) and men not achieving (MN = 10)). The achievement of PA was determined by total Metabolic Equivalent (MET) – Minute/week ≥ 600. Cognition, health-related quality of life, falls history and health status was measured. Results: Women had poorer performance in time, gait velocity and stride length regardless of PA level. The cognitive condition had the greatest effect on gait parameters in all groups, except for stride length which decreased more under the motor condition. Women who did not achieve the PA guidelines had poorer perceived health-related quality of life than men who achieved and did not achieve the guidelines. Conclusions: The findings suggest that women, regardless of PA level, experience greater deterioration under ST and DT conditions in 10-meter walk and TUG tests in terms of time and gait measures such as velocity and stride length. This interplay cannot be explained by PA alone since it could be reflective of poorer perceived health and frailty in older women. These findings are considered of importance when planning DT and PA interventions that aim to increase PA levels and promote function in older women.